Antioxidant potential of some species of the genus bomarea (Alstroemeriaceae) (2011)
ABSTRACT: This work evaluated the antioxidant activity of ethanol extracts from 11 species of the genus Bomarea (Alstroemeriaceae) by means of two in vitro methods. Values of CE50 between 51 and 333 µg/mL were obtained for DPPH the test, and the highest activity levels were found for B. glaucescens, B. setacea, B. pardina and B. euryantha, which presented a similar CE50 or lower than the reference used, silymarin (70.6 ug/mL). Likewise, the TBARS method showed that the maximum inhibition of lipid peroxidation of the linoleic acid was produced by B. hirsuta (malondialdehyde = 0.429 µM), followed by B. bredemeyerana (0.474 µM), B. callejasiana (0.479 µM), B. euryantha (0.489 µM), B. glaberrima (0.497 µM), and B. setacea (0.500 µM). Additionally, the concentration of phenol compounds was evaluated by the Folin-Ciocalteau method, finding that B. setacea presented the highest content of these (159.75 gallic acid equivalents/mg of extract). Bomarea setacea showed the highest antioxidant properties demonstrated by its free-radical scavenging and significant inhibition capacity of the oxidation of linoleic acid.